Technology education students: E-tutors for school children - Johnson, Genevieve; Bratt, S. (Blackwell Publishing, 2009)
E-tutoring refers to individualised learning support mediated by Internet technology. While increased demand for tutors has led to a surge in commercial e-tutoring services, volunteer e-tutoring programs for children are rare. To test the viability of volunteer e-tutoring for elementary school students, 10 undergraduate students enrolled in a technology education (TE) course provided online with instructional support to children in need of tutoring services. Each e-tutor was assigned a specific child, developed a Web Course Tools course and corresponding online activities to improve teacher-identified skill deficiencies, and provided 8 weeks of e-tutoring. Three video conferences complemented online instructional interaction between e-tutor and e-tutee. Children, parents and TE students expressed positive evaluation of the initiative.